2023
DOI: 10.21763/tjfmpc.1192151
|View full text |Cite
|
Sign up to set email alerts
|

Rational Drug Use Status of Students at a University Hospital

Abstract: Objective: Irrational drug use is a significant global and public health issue, including in Turkey Turk. This study aims to assess the knowledge and attitudes of students toward rational drug use . Methods: The study population comprised of 1909 students enrolled in Bakırçay University's 2019-2020 academic year. The sample size of the study was 780 students selected through stratified random sampling from each faculty. Data were collected using the "Rational Drug Use Form," which included demographic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Furthermore, ORS emerged as a crucial choice for managing diarrhea in our study. Similar reports were quoted by Devy et al [34] and Sylvia et al [35] that ORS is commonly used for the self-medication of diarrhea.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, ORS emerged as a crucial choice for managing diarrhea in our study. Similar reports were quoted by Devy et al [34] and Sylvia et al [35] that ORS is commonly used for the self-medication of diarrhea.…”
Section: Discussionsupporting
confidence: 82%
“…most common antibiotic resulting in adverse drug reactions, followed by tablet azithromycin [30]. Another study found that the use of the norfloxacin+metronidazole combination can lead to adverse effects commonly associated with norfloxacin, such as mild nausea, vomiting, and diarrhea [35]. Fixed dose combinations (FDCs) can improve patient compliance and decrease pill burden, but irrational prescribing of FDCs is a major health concern [40].…”
Section: Mishra Et Almentioning
confidence: 99%